Design and Evaluation of a Small-Scale Hydraulic Cocoa Press Machine - Irawan, Andik Irawan.,; Tyagita, Dicky Adi; Asmono, Sepdian Luri; Hastutik, Septi Dwi (Teknotan: Jurnal Industri Teknologi Pertanian, 2025)
Cocoa is crucial for Small and Medium Enterprises (SMEs), facilitating the production of primary and secondary cocoa-based products, including various chocolate derivatives. This study aims to design and evaluate a small-scale hydraulic cocoa press suitable for SME applications by examining the effects of temperature and material mass on extraction yield. These factors form the basis for developing an efficient press machine for small to medium-scale production. The research involved a theoretical machine design followed by experimental testing using three temperature levels (90°C, 100°C, and 110°C) and three material capacities (150 g, 200 g, and 250 g). Results indicated that temperature was the primary factor affecting extraction performance. A temperature of 110°C consistently yielded the highest extraction, reaching 25% at 150 g and staying above 17% at 250 g. Lower temperatures (90°C and 100°C) produced significantly lower yields, with minimal gains despite increased material amounts. These findings offer a strong technical foundation for designing a more efficient cocoa press with an integrated heating system to maintain optimal operating temperature. Implementing this machine in SMEs could enhance production efficiency, reduce processing losses, and increase the added value of cocoa products, thereby strengthening SME competitiveness in the agro-industrial sector.